Factors Associated With Mortality Among the COVID-19 Patients Treated at Gulu Regional Referral Hospital: A Retrospective Study - Baguma, Steven; Okot, Christopher; Alema, Nelson Onira; Apiyo, Paska; Layet, Paska; Acullu, Denis; Oloya, Johnson Nyeko; Ochula, Denis; Atim, Pamela; Olwedo, Patrick Odong; Okot, Smart Godfrey; Oyat, Freddy Wathum Drinkwater; et al. (Frontiers in Public Health, 2022)
Background The advent of the novel coronavirus disease 2019 (COVID-19) has caused millions of deaths worldwide. As of December 2021, there is inadequate data on the outcome of hospitalized patients suffering from COVID-19 in Africa. This study aimed at identifying factors associated with hospital mortality in patients who suffered from COVID-19 at Gulu Regional Referral Hospital in Northern Uganda from March 2020 to October 2021. Methods This was a single-center, retrospective cohort study in patients hospitalized with confirmed SARS-CoV-2 at Gulu Regional Referral Hospital in Northern Uganda. Socio-demographic characteristics, clinical presentations, co-morbidities, duration of hospital stay, and treatments were analyzed, and factors associated with the odds of mortality were determined. Results Of the 664 patients treated, 661 (99.5%) were unvaccinated, 632 (95.2%) recovered and 32 (4.8%) died. Mortality was highest in diabetics 11 (34.4%), cardiovascular diseases 12 (37.5%), hypertensives 10 (31.3%), females 18 (56.3%), ≥50-year-olds 19 (59.4%), no formal education 14 (43.8%), peasant farmers 12 (37.5%) and those who presented with difficulty in breathing/shortness of breath and chest pain 32 (100.0%), oxygen saturation (SpO2) at admission <80 4 (12.5%), general body aches and pains 31 (96.9%), tiredness 30 (93.8%) and loss of speech and movements 11 (34.4%). The independent factors associated with mortality among the COVID-19 patients were females AOR = 0.220, 95%CI: 0.059–0.827; p = 0.030; Diabetes mellitus AOR = 9.014, 95%CI: 1.726–47.067; p = 0.010; Ages of 50 years and above AOR = 2.725, 95%CI: 1.187–6.258; p = 0.018; tiredness AOR = 0.059, 95%CI: 0.009–0.371; p < 0.001; general body aches and pains AOR = 0.066, 95%CI: 0.007–0.605; p = 0.020; loss of speech and movement AOR = 0.134, 95%CI: 0.270–0.660; p = 0.010 and other co-morbidities AOR = 6.860, 95%CI: 1.309–35.957; p = 0.020. Conclusion The overall Gulu Regional Hospital mortality was 32/664 (4.8%). Older age, people with diabetics, females, other comorbidities, severe forms of the disease, and those admitted to HDU were significant risk factors associated with hospital mortality. More efforts should be made to provide “additional social protection” to the most vulnerable population to avoid preventable morbidity and mortality of COVID-19 in Northern Uganda.